Seeing Ourselves Through Technology How We Use Selfies, Blogs and Wearable Devices to See and Shape Ourselves - Rettberg, Jill W. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book is open access under a CC BY license. Selfies, blogs and lifelogging devices help us understand ourselves, building on long histories of written, visual and quantitative modes of self-representations. This book uses examples to explore the balance between using technology to see ourselves and allowing our machines to tell us who we are.